Key factors that influence performance of workers: a study in an inter-national corporation - (Human Resources Department in Media Prima Berhad) / Nur Liyana Mohamad Arifin - Mohamad Arifin, Nur Liyana (Faculty of Business and Management, 2009)
This study was carried out determine the key factors influence employee’s performance in Media Prima Berhad (MPB). Besides, this study is to identify the level of performance, to identify the relationship between the factors and the performance, to determine the significance differences in performance among gender and to identify factors those explain the most towards performance. The researcher collected the information from the questionnaires that has distributed to the employees in Human Resources Department in Media Prima Berhad (MPB). The overall finding of this study indicates that there have a significant relationship between factors identified and performance and there is no significant different among gender towards performance. From the study can conclude that the factors influence performance among workers in Media Prima Berhad has the two factors, that are performance feedback and workplace incentives explain significantly towards performance. Media Prima Berhad needs to do the best strategic management to survive in these markets especially during this unstable economic situation. This company needs to take the effective action in order to make their worker can perform their best. it is really important because Media Prima Berhad have to competed with their own competitors. So, from this study it will help us in order to determine and ensure that which factors are mostly influence the performance among workers and to identify the effective actions in order to make all the dreams come true and to achieve our Mission and Vision.